Lasting pure-motor deficits after focal posterior internal capsule white-matter infarcts in rats - Blasi, Francesco (J Cereb Blood Flow Metab, 2015)
Small white-matter infarcts of the internal capsule are clinically prevalent but underrepresented among currently available animal models of ischemic stroke. In particular, the assessment of long-term outcome, a primary end point in clinical practice, has been challenging due to mild deficits and the rapid and often complete recovery in most experimental models. We, therefore, sought to develop a focal white-matter infarction model that can mimic the lasting neurologic deficits commonly observed in stroke patients. The potent vasoconstrictor endothelin-1 (n=24) or vehicle (n=9) was stereotactically injected into the internal capsule at one of three antero-posterior levels (1, 2, or 3 mm posterior to bregma) in male Sprague-Dawley rats. Endothelin-injected animals showed highly focal (~1 mm(3)) and reproducible ischemic infarcts, with severe axonal and myelin loss accompanied by cellular infiltration when examined 2 and 4 weeks after injection. Only those rats injected with endothelin-1 at the most posterior location developed robust and pure-motor deficits in adhesive removal, cylinder and foot-fault tests that persisted at 1 month, without detectable sensory impairments. In summary, we present an internal capsule stroke model optimized to produce lasting pure-motor deficits in rats that may be suitable to study neurologic recovery and rehabilitation after white-matter injury.